Incidence and risk factors of postoperative complications following periodontal flap surgery: a retrospective study - Gu, Hongjiang; Liu, Wei; Xu, Xiaoyu; Shen, Yinjie (Frontiers in Dental Medicine, 2025)
BackgroundPeriodontal flap surgery is a common procedure for treating advanced periodontal disease, but postoperative complications such as pain, infection, and delayed healing are frequent. This study aims to investigate the incidence of postoperative complications and identify key risk factors, contributing to more personalized surgical management.MethodsA retrospective analysis was conducted on 121 patients who underwent periodontal flap surgery. Patient demographics, clinical data (e.g., age, probing depth, clinical attachment loss), and surgical variables (e.g., incision type, surgery duration) were collected. Logistic regression analysis was performed to identify significant predictors of postoperative complications. The complications analyzed included dentin hypersensitivity, excessive pain, infection, and gingival bleeding.ResultsPostoperative complications occurred in 44.63% of patients. Age was a significant predictor, with each additional year increasing the risk of complications by 12% (p < 0.001). Clinical attachment loss was strongly associated with complications (p = 0.009). Semilunar incisions, typically used in localized mild cases, were associated with a lower incidence of complications compared to trapezoidal incisions (p < 0.001). Smoking also significantly increased the risk of complications in both the univariate and multivariate analyses (p < 0.05). In the univariate analysis, both preoperative antibiotics and preoperative analgesics were associated with a reduced risk of complications (p < 0.05), but these effects were not significant in the multivariate analysis (p > 0.05).ConclusionThis study highlights age, clinical attachment loss, smoking, and surgical incision type as significant predictors of postoperative complications following periodontal flap surgery. The findings underscore the need for personalized surgical approaches, particularly in older patients and those with severe periodontal disease.